Changes in the volatile constituents of the leaves of Stevia rebaudiana Bertoni caused by different drying procedures - Olusegun, Lasekan; Reddi, Kalla; Naidu, Mohan (WFL Publisher, 2013)
Changes in the volatile constituents and the structural integrity of dried stevia leaves (Stevia rebaudiana Bertoni) were evaluated. A gas chromatography-mass spectrometry analysis of the compounds revealed a wide variety of various chemical compounds. Among the component compounds, 2 diterpene alcohols, 7 sesquiterpenes, 4 triterpenes, a sesquiterpene oxide and 10 non-terpene compounds were identified. The major compounds were betulin, α-amyrin and the cyclopropyl ursane-type triterpene, 13,27-cycloursan-3-ol, acetate (3β,13β,14β). With the exception of the cyclopropyl ursane-type triterpene, trans-squalene and longifolenaldehyde, oven-drying significantly (P < 0.05) reduced the volatile constituents in the dried leaves. Scanning results showed that oven-drying method significantly affected the structural integrity of the leaves.